Perkembangan Minat Masyarakat pada Madrasah Aliyah di Kota Gorontalo - Luneto, Buhari (Nadwa, 2014)
The Act No. 20, 2003 of National Education System explains that Madrasah Aliyah as an Islamic educational institution has been equated with other public schools. This equivalence does not change automatically the public of Gorontalo perception toward Madrasah Aliyah as a second choice. Such perception affects the community interest to send their children to Madrasah Aliyah. However, Madrasah Aliyah in Gorontalo still has great prospect in the future. So some very urgent improvement and imaging is performed by Madrasah Aliyah. This improvement is very important because most people see Madrasah Aliyah as second-class school and its graduates do not have brilliant future. In fact, Madrasah Aliyah can create human resources who have intact insight, are divinity insight, social insight and scientific insight.